The Impact of Health Promotion about E-cigarettes Risk among Adolescents - Dian Mawarni; Shofiyatul Masyiyah; Anis Yunita; Nazira Dyah Maharani (Preventia : The Indonesian Journal of Public Health, 2023)
The increasing prevalence of cigarette users in the younger generation is clear evidence that cigarettes are increasingly popular, especially e-cigarettes. Misinformation and misperceptions circulating in the community as well as the role of the media add to concerns about the impact that e-cigarettes can have. Therefore, a transformation of health promotion efforts to save future generations from the dangers of e-cigarettes is needed. This study aimed to analyze the effect of health promotion media in reducing the willingness to smoke e-cigarettes in adolescents. This study used a quantitative analytic design with primary data. The instrument used was a questionnaire which was filled out independently by the respondents. Data collection was carried out online using a small group trial. Data analysis was using Mc Nemar test. The bivariate analysis showed that the three challenges had an impact in the form of increasing knowledge and perceptions. On the knowledge variable, the whole challenge gave a significant increase with the results of sig. 0.025 on the challenge of providing visual media socialization, sig. 0.014 on the challenge of providing audio-visual media socialization, and sig. 0.008 on the active participation challenge. Adolescent perceptions also increased before and after a series of challenges was given. The provision of health promotion with these three challenges had a significant difference of sig. 0.031 on adolescent perceptions. There were differences in adolescent knowledge and perceptions of e-smoking behavior through the using of health promotion media. The most effective method used in changing the knowledge and perceptions of adolescents is to use the active participation of adolescents.